Nilai-Nilai Pendidikan Akhlak Tasawuf Dalam Lakon Ma’rifat Dewa Ruci - Abbas, Ngatmin; ., Sukari; Alhasbi, Faruq (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This research delves into the values of Sufi education within the puppet play "Ma'rifat Dewa Ruci." Through the analysis of key scenes, the study discusses the applicability of Sufi values in the context of modern education. Content analysis is employed to unveil the meanings and implications of each scene, while a phenomenological approach is used to understand the perspectives of characters in the play. The research findings indicate that Sufi values such as asceticism, trust in God (tawakal), and spiritual knowledge (ma'rifat) can be implemented in shaping individual character and spirituality. The implications of this research encompass the potential contribution to the development of a character education curriculum based on Sufi values in educational institutions.